Skills Learnt in Youth Work Practice Necessary for the Digital age: A Qualitative Study of NEET Youth - Chauke, Thulani Andrew (Research in Social Sciences and Technology- OpenED Network, 2024)
Not in education, employment and not in training (NEET) youth as vulnerable groups need to learn and relearn new set of skills needed for the digital age since traditional jobs will be replaced with new jobs that will demand a new set of skills. The study aims to explore the perspectives of NEET youth on the skills they had learnt in youth work practices that are necessary for the digital age. A qualitative approach was employed to guide the gathering and analysis of the data. Some of the skills learnt in youth work practices include business acuity, digital skills, active citizens, and teamwork skill. To improve youth work practices in the digital age, this study recommends that youth workers need to have intensive knowledge so they can implement youth work activities effectively and improve the outcomes of NEET youth in the digital age.